Effect of oat bran on time to exhaustion, glycogen content and serum cytokine profile following exhaustive exercise - Frollini Anelena B; Prestes Jonato; Donatto Felipe F; Palanch Adrianne C; Verlengia Rozangela; Cavaglieri Claudia (Taylor & Francis Group, 2010)
Abstract The aim of this study was to evaluate the effect of oat bran supplementation on time to exhaustion, glycogen stores and cytokines in rats submitted to training. The animals were divided into 3 groups: sedentary control group (C), an exercise group that received a control chow (EX) and an exercise group that received a chow supplemented with oat bran (EX-O). Exercised groups were submitted to an eight weeks swimming training protocol. In the last training session, the animals performed exercise to exhaustion, (e.g. incapable to continue the exercise). After the euthanasia of the animals, blood, muscle and hepatic tissue were collected. Plasma cytokines and corticosterone were evaluated. Glycogen concentrations was measured in the soleus and gastrocnemius muscles, and liver. Glycogen synthetase-α gene expression was evaluated in the soleus muscle. Statistical analysis was performed using a factorial ANOVA. Time to exhaustion of the EX-O group was 20% higher (515 ± 3 minutes) when compared with EX group (425 ± 3 minutes) (p = 0.034). For hepatic glycogen, the EX-O group had a 67% higher concentrations when compared with EX (p = 0.022). In the soleus muscle, EX-O group presented a 59.4% higher glycogen concentrations when compared with EX group (p = 0.021). TNF-α was decreased, IL-6, IL-10 and corticosterone increased after exercise, and EX-O presented lower levels of IL-6, IL-10 and corticosterone levels in comparison with EX group. It was concluded that the chow rich in oat bran increase muscle and hepatic glycogen concentrations. The higher glycogen storage may improve endurance performance during training and competitions, and a lower post-exercise inflammatory response can accelerate recovery.